Perancangan Sistem Kebangkrutan Menggunakan Metode Altman Z-score - Cristeddy Asa Bakti; Anton Anton (Elkom: Jurnal Elektronika dan Komputer, 2021)
The purpose of this study is to produce a design to predict, analyze and determine the level of potential bankruptcy of a company using the Altman Z-Score method. Predictions are made by analyzing the financial statements of a company. The research approach used is a qualitative approach. Data analysis technique in this research is descriptive analysis technique. The results of the first phase of research are in the form of a review of bankruptcy prediction analysis using secondary data from banks in Indonesia that are already on the stock exchange and have branch offices in the city of Semarang, while the second year produces an information system design that has added value from the first year to the third year. testing the system that has been designed using actual financial statement data.